Utilization of Social Media as a Communication Tool in Health Promotion - Nuzulattibyani, Dania; Febriani, Sari Indah; Afria, Rengki (Proceeding International Conference on Malay Identity, 2023)
Social media has become an effective communication tool in health promotion efforts. In today's digital age, the use of social media has increased among the public, making social media platforms useful for disseminating health information and encouraging people to adopt healthier lifestyles. In this article, we explore what is unique about social media, as well as its challenges. In health promotion, the use of social media has a huge advantage as it allows you to reach a wider audience. With millions of users active on various social media platforms such as Facebook, Instagram, and Twitter, it is easy to send health messages to thousands of people within seconds. Social media also allows the public and health information providers to interact directly, which allows for fruitful discussions and advice to be given in real-time. Abstrak Media sosial telah menjadi alat komunikasi yang efektif dalam upaya promosi kesehatan. Dalam era digital saat ini, penggunaan media sosial telah meningkat di kalangan masyarakat, menjadikannya platform di media sosial berguna untuk menyebarkan informasi tentang kesehatan dan mendorong masyrakag untuk menerapkan gaya hidup yang lebih sehat. Dalam artikel ini, kami menjelajahi apa saja keunikan yang dimiliki oleh media sosial, besertan tantangannya. Dalam promosi kesehatan, penggunaan media sosial memiliki keuntungan besar karena memungkinkan Anda menjangkau khalayak yang lebih luas. Dengan jutaan pengguna yang aktif di berbagai platform media sosial seperti Facebook, Instagram, dan Twitter, adalah mudah untuk mengirimkan pesan kesehatan ke ribuan orang dalam hitungan detik. Media sosial juga memungkinkan masyarakat dan penyedia informasi kesehatan berinteraksi secara langsung, yang memungkinkan diskusi yang bermanfaat dan saran yang diberikan secara real-time.